Homemakers Alias Families and Consumers - Nellie R. McCannon (Journal of Applied Communications, 1971)
An apple is an apple is an apple—to paraphrase Gertrude Stein in her statement about a rose. Maybe you think an apple is an apple, too. That it's refreshing to eat and gives you good food value for the money. But that's not necessarily the way the HOMEMAKER audience sees it.